Empowering Kindergarten Teachers to Teach English Speaking Skills through the Singing Method at TK Al-Aqobah II (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
English is important in global education, so teaching it early helps children build strong language skills. One approach to teaching English is the singing method, which is effective and engaging because it utilizes repetition and rhythm to enhance memory and encourage participation. Teachers at TK Al-Aqobah II recognize the importance of English instruction but face challenges in implementation. Therefore, they require support to effectively apply methods like singing to improve students’ speaking skills. This community service project aims to empower teachers to teach English speaking skills through the Singing Method at TK Al-Aqobah II. The program was conducted through the training session, model teaching demonstration, and mentoring activity. The implementation revealed that the teachers demonstrated increased confidence in using English during lessons, and students responded positively with improved participation and pronunciation. This method also fostered a more engaging and joyful learning atmosphere, making English more accessible and enjoyable for young learners. Overall, the activity successfully strengthened the teachers’ capacity to deliver effective and interactive English speaking lessons.